32. ADDRESSING METHODOLOGICAL CHALLENGES IN CIAS TO ENHANCE CLINICAL TRIAL SUCCESS. (9th April 2019) - Granger, Kiri
Abstract: Cognitive impairment is common in patients with schizophrenia, with deficits frequently observed across both neurocognitive and social cognitive tasks. Cognitive dysfunction is among the strongest determinants of poor social and occupational functioning in this population, indicating that these deficits represent an important unmet target for therapeutic intervention. Despite considerable efforts by pharmaceutical companies, there are currently no drugs that have been approved for the amelioration of these deficits in schizophrenia. A series of compounds have demonstrated early promise, only to have failed at the later stages of development. It remains a matter of debate whether this is truly due to the compounds being ineffective, or whether trial methodology itself has been a limiting factor in successfully demonstrating the efficacy of these agents. Key methodological limitations of existing trials, to be discussed, include a multitude of factors around patient selection, such as level of cognitive impairment, age, symptom severity and current plus existing medical history and medication. Product-specific data is gradually becoming available, to build an evidence base which suggests not all patients meeting the DSM-V diagnostic criterion for schizophrenia should be included in trials targeting cognitive impairment associated with schizophrenia (CIAS). Several stakeholders, including regulatory agencies and payers, are increasingly interested in exploring and understanding ways to enhance the outcome of CIAS trials to see the approval of an effective pharmacological agent reach the market. This symposia will hear from four presenters to discuss 1) a brief history of CIAS trials and the current consensus on patient selection (Dr Jack Cotter); 2) lessons learnt from the successes and failures in these trials, including regulatory considerations (Dr Steve Brannan, Karuna Pharmaceuticals); 3) a post-hoc analysis of a large Phase II multi-national trial (Dr Kiri Granger, on behalf of Boehringer Ingelheim); 4) a novel compound entity currently in development & methodological/statistical adaptations made to this drug development program (Dr Charles Large, Autifony Therapeutics). Chief Scientific Officer at Cambridge Cognition, Dr Jenny Barnett, will be the discussant for this symposia panel to summarize, what we have learnt so far in CIAS trials, the status of the current evidence base to guide decision making and what the future of drug development and post-marketing approval for CIAS potentially holds. We hope this symposia will be both educational and thought provoking by providing useful, evidence-based, considerations for the design of future studies to enhance CIAS trial success. Advances in this area are likely to hold direct 'real world' benefits for patients and their families, while also reducing the financial burden of the disorder on society. The lessons learned and recommendations discussed here could also improve the efficacy and outcome of clinical trials for other serious mental health illnesses in which cognitive dysfunction is a core and debilitating feature.